Let freedom sing [videorecording (DVD)] : how music inspired the civil rights movement - Goodman, Jon, 1952 August 20-; Gossett, Louis, Jr., 1936- (Time Life : Direct Holdings Americas Inc., 2009)
One of the most powerful movements in American history is told through the singers and songwriters who fought for change with their music. Highlights include the influence of WDIA radio in Memphis and the influence of Harry Belafonte, Phil Ochs and other performers.